PENGARUH TERPAAN IKLAN BUKALAPAK VERSI â€œBELANJA GILA HARGA SAKIT JIWAâ€ DI TELEVISI TERHADAP MINAT BELI MAHASISWA DI UNIVERSITAS RIAU - Ikhsan, Muhamad; Lubis, Evawani Elysa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Development of technology make a change on promotion activity. In the beginning only door to door, but now more efficient because of utilise print media or electronic media. One of a company use an electronic media to promote their product is Bukalapak, they are promote a new characteristic that is negotiation of price on television. The main goal of this research is to know an influence of Bukalapak advertising on television toward buying interest of students in Riau University. The theory in this research is Theory of S-R (Stimulus â€“ Response). The method used in this research was descriptive quantitative with used accidental sampling technique and total of sample as many as 96 respondents. Technique of data accumulation in this research did by way of spread a questionnaire directly to respondents. To know an influence between X variable and Y variable, researcher used analysis of simple regression linear and to process the data result of questionnaire, researcher used SPSS Program for Windows version 23. Based on result of simple regression linear in this research, coefficient of regression value is Y = 22,104 + 0,806 X by significance level 0,000. Definitely smaller than Î± = 0,05. Concluded Ha accepted and H0 rejected, so there is an influence of Bukalapak advertising on television toward buying interest of students in Riau University as big as 20% dan classified category of weak. This is because television is not a main media for student to obtain an information, they are choose smartphone for internet access to satisfy information needed. Keywords : Influence Attack, Advertising, Buying Interest